Paradigma Belajar dalam Perspektif Al-Qur’an Surat Al-‘Alaq: Studi Komparatif Tafsir Al-Misbah dan Ibnu Katsir - Sri Dwi Cahya Ningsih; Ahmad Fauzi; Saiful Islam (Kartika: Jurnal Studi Keislaman, 2026)
The current state of Islamic education faces a crisis of values ​​and demonstrates a shift in the very meaning of learning. The learning process tends to prioritize outcomes and grades exclusively, rather than the transformation of knowledge, spirituality, and character. If this trend persists, it will produce individuals who are intellectually brilliant but spiritually and morally weak. Stemming from this concern, this study was conducted to re-examine the concept of learning based on the perspective of the Qur'an. The primary sources for this research are the Tafsir Al-Misbah and Tafsir Ibnu Katsir; by comparing these two exegeses, the study aims to formulate a learning paradigm that aligns with Qur'anic values. This research employs a qualitative methodology, specifically utilizing a library research approach. The findings reveal both similarities and differences between the two exegeses, particularly in their interpretation of the term iqra. Tafsir Al-Misbah offers a broader, more comprehensive, and detailed interpretation, whereas Tafsir Ibnu Katsir interprets iqra in a more concise and straightforward manner. Based on this analysis, the learning paradigm from a Qur'anic perspective encompasses a range of learning activities, including: reading, comprehending, studying, analyzing, examining, and developing knowledge